Measuring the Brand Loyalty of Unsatisfied Telkomsel Flash Customer - Siahaan, Efraldo Sugih M; Iskandar, Budi Permadi (Journal of Business and Management, 2013)
Telkomsel is one of the largest telecommunication company in Indonesia which provides a wide range of services to its customers. competing with Indosat and Smartfren with a total market share of 77.5%. Indonesia is the 5th biggest Twitter social media users in the world with 19.5 million users. The purpose of this study is to measure brand loyalty of customers who feel a disatisfaction in experiencing Telkomsel Flash product. Basic understanding of the brand, brand equity, brand loyalty, social media, content analysis, and public relations are the theories related. Kurrently.com and Topsy.com are research helping tools in analyzing social media content other than using Twitter.com. The methodology contains of research framework and determining sampling method. Slovin Theory is used in determining the number of samples. There are 4 parts presented in data analysis. Finally, conclusion and recommendation were written based on data analysis and several necessary facts.Â Keywords : Telkomsel Flash, Brand Loyalty, Content Analysis, Social Media, Twitter